El escultor José Rodríguez Díaz, "Sócrates" (h. 1746-1817) - Cruz Yábar, María Teresa (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2002)
El escultor gallego José Rodríguez Díaz (San Pedro de Sesterey, Lugo h. 1746-La Carraca. Cádiz 1817), formado en la Real Academia de Bellas Artes de San Fernando entre 1766 y 1785, destacó como retratista de importantes personajes de la Corte. En este trabajo se dan a conocer su vida y obra, se identifican como suyos el busto del Conde de Flohdablanca (Museo del Prado) y los de Manuel Ventura Figueroa y Miguel de Múzquiz (Real Academia de San Fernando), así como un par de relieves que existen en esta institución; se añaden a su catálogo obras desaparecidas como los modelos de Pelayo y Favila, dos leones y dos trofeos que decoraban la fachada del Monumento de Covadonga diseñado por Ventura Rodríguez, y un busto de Pedro Rodríguez de Campomanes. The Galician Sculptor José Rodríguez Díaz (San Pedro de Sesterey, Lugo h. 1746-La Carraca, Cádiz 1817), who learntin the spanish San Fernando Royal Academy of Art in Madrid between 1766 and 1785, stood out as portrait Sculptor of outstanding members of the royal court. In this article about his Ufe and artistic career, some pieces have been identified as his work: The bust of the Count of Floñdablanca (Prado Museum), and those of Manuel Ventura Figueroa and Miguel de Múzquiz (Real Academia de San Fernando), as well as some reliefs owned by the same institution. Furthermore, six models belonging to Pelayo and Favila, to a couple of lions and to two throphies, which decorated the facade of the Monument of Covadonga —designad by Ventura Rodríguez— and a bust of Pedro Rodríguez de Campomanes, all missing, are included in the sculptors catalogue.